MRI of subcutaneous granuloma annulare: A series of four cases - Jug Liona; Rupreht Mitja (Acta Medico-Biotechnica, 2023)
Background: Subcutaneous granuloma annulare (SGA) is a rare benign soft tissue mass that occurs mostly in the lower limbs of young children. Detailed knowledge of imaging findings is needed to avoid unnecessary invasive diagnostic procedures. Materials and Methods: One follow-up case and three companion cases are presented. All children were between the ages of 5 and 10 years. Results: The MRI findings demonstrated ill-defined subcutaneous masses in three cases while in one case the mass was mildly hypointense and heterogeneous on fluid-sensitive sequences. Contrast agent was administered intravenously only in one case, where moderate enhancement was observed. Conclusion: Detailed clinical description of the lesion location was crucial. In addition, knowledge of MR imaging findings was necessary for a correct diagnosis to reassure the parents and avoid unnecessary invasive diagnostic procedures.